2004
DOI: 10.1152/jn.00976.2003
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Muscle Activity Underlying Object-Specific Grasp by the Macaque Monkey

Abstract: During object grasp, a coordinated activation of distal muscles is required to shape the hand in relation to the physical properties of the object. Despite the fundamental importance of the grasping action, little is known of the muscular activation patterns that allow objects of different sizes and shapes to be grasped. In a study of two adult macaque monkeys, we investigated whether we could distinguish between EMG activation patterns associated with grasp of 12 differently shaped objects, chosen to evoke a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
127
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 37 publications
(41 reference statements)
10
127
0
Order By: Relevance
“…Such a force configuration might effectively be planned in advance using the sEMG signal of a human subject, for instance during teleoperation, mapped onto the dynamics of the robotic gripper. Indeed, in [6] it was shown that different EMG signals related to different objects differed not only during grip but also during the reaching movement towards the object;…”
Section: Kinematic and Muscle Synergiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a force configuration might effectively be planned in advance using the sEMG signal of a human subject, for instance during teleoperation, mapped onto the dynamics of the robotic gripper. Indeed, in [6] it was shown that different EMG signals related to different objects differed not only during grip but also during the reaching movement towards the object;…”
Section: Kinematic and Muscle Synergiesmentioning
confidence: 99%
“…In particular in [27] it was shown that three synergies accounted for 81% of the sEMG variance, but the analysis performed was time-dependent, meaning that synergies are short temporal profiles of activation rather than single sEMG samples. In this work we concentrate on a simpler PCA-based dimensionality reduction (which is the type effectively used in [7] as well as, e.g., in [29]) and obtain quantitatively similar results, that is, as far as the amount of variance is concerned.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…We investigate the usability of this information from forearm sEMG signals. Brochier et al (2004) were able to distinguish between different objects by using EMG-signals recorded from electrodes implanted in the hand, arm, and finger muscles of monkeys. They showed that the recorded signals were different for each object during a reaching movement as well as during a grasp.…”
Section: Introductionmentioning
confidence: 99%
“…The problems of relating the activity of various muscles to the mechanics of the grasping hand are complex (Schaffelhofer et al 2015;Towles et al 2013;ValeroCuevas 2005;Valero-Cuevas et al 2003). Nevertheless, when 6 -8 objects, which differ in size and shape, are all presented at the same location, the object that is being grasped can be decoded from the EMG activity of 8 -12 forearm and intrinsic hand muscles (Brochier et al 2004;Fligge et al 2013). The decoding accuracy increases progressively during the movement, approaching 100% correct object classification midway through the reach, indicating that patterns of activation across the set of distal muscles become more object specific as the movement evolves.…”
mentioning
confidence: 99%